2014
DOI: 10.1097/ico.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Lattice Corneal Dystrophy Without Typical Lattice Lines Caused by a Novel Mutation in the TGFBI Gene

Abstract: The mutant codon 565 is located at the C-terminus in the region corresponding to a highly conserved amino acid in the fourth fascilin domain of the TGFBI protein. The novel variant expands the spectrum of TGFBI mutations causing LCD and located in this region. An increased number of known mutations will facilitate future studies of genotype-phenotype correlations and molecular pathogenesis of corneal dystrophies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…TGFβIp-associated corneal dystrophies are phenotypically heterogeneous, inherited in an autosomal dominant manner 1 9 10 and are classified as lattice, granular, combined lattice and granular, Reis-Buckler and Thiel-Behnke corneal dystrophies 1 2 11 12 . So far, 64 single amino acid mutations associated with distinct phenotypes have been reported 4 13 14 . Among the four FAS1 domains of TGFβIp, the 1 st and 4th FAS1 domains carry the disease related mutations, with ~80% of the mutations residing in the 4 th _FAS1 domain 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TGFβIp-associated corneal dystrophies are phenotypically heterogeneous, inherited in an autosomal dominant manner 1 9 10 and are classified as lattice, granular, combined lattice and granular, Reis-Buckler and Thiel-Behnke corneal dystrophies 1 2 11 12 . So far, 64 single amino acid mutations associated with distinct phenotypes have been reported 4 13 14 . Among the four FAS1 domains of TGFβIp, the 1 st and 4th FAS1 domains carry the disease related mutations, with ~80% of the mutations residing in the 4 th _FAS1 domain 11 .…”
mentioning
confidence: 99%
“…In lattice corneal dystrophies (LCD), the protein aggregates appear as lattice lines or amyloid fibrils (amyloidogenic). In granular corneal dystrophies (GCD), they appear as granular, non-amyloidogenic deposits 11 12 13 14 15 16 . Both phenotypes display significant differences in morphology, aggregation and tinctorial properties.…”
mentioning
confidence: 99%
“…Immunohistochemical corneal analysis from a p.(L558P) carrier revealed the amyloidal nature of the deposits, supporting its classification as LCD. Several studies have also reported atypical LCD phenotypes associated with different TGFBI variants, which are characterized by a delayed onset of the clinical signs and symptoms (p.[P501T], p.[L527R], p.[L565P], p.[H626R] and p.[N622H]) and/or deep location of the amyloid deposits in the corneal stroma gene (p.[R496W], p.[L527R], p.[A546D], p.[G594 V] and p. [V631D]).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, 69 disease-associated variants in the transforming growth factor beta-induced gene (TGFBI, OMIM 601692) have been described as being involved in different CD subtypes in patients. The IC3D classi cation describes TGFBI-linked dystrophies by the recognizing that they affect multiple layers rather than being con ned to one corneal layer (7)(8)(9)(10)(11)(12)(13)(14). Several phenotypes have been described according to corneal layer alterations and the investigation of pathogenic mutations in the TGFBI gene, with the exception of metabolic effects.…”
Section: Introductionmentioning
confidence: 99%